Reorienting Islamic Jurisprudence Curriculum in Pesantrens for Generation Z: A Systematic Literature Review - Machmudi Mukson; Imam Subhi (Al-Qalam Institue, 2026)
This study aims to analyze the reorientation of the pesantren fiqh curriculum to address contemporary religious issues encountered by Generation Z while maintaining the foundations of classical Islamic jurisprudence. A qualitative approach with a Systematic Literature Review (SLR) design was employed. Relevant literature published primarily from 2019–2026 was identified, examined, compared, and synthesized using thematic analysis through data condensation, data display, and data verification. The findings indicate that the reorientation of fiqh education requires integration of classical fiqh, usul al-fiqh, qawāʿid fiqhiyyah, and maqāṣid al-sharīʿah with contemporary religious issues, digital religious literacy, and contextual learning. The study identifies digital transactions, social-media ethics, fragmented religious information, changing religious authority, religious polarization, technological development, and identity formation as important areas for curriculum contextualization. The study proposes a conceptual framework that positions classical fiqh as the foundation, Islamic legal methodology as the analytical framework, Generation Z issues as the contextual basis, and contextual learning as the curricular orientation. This framework can support pesantren in developing fiqh education that is more analytical, relevant, digitally aware, and responsive while preserving its Islamic scholarly tradition.